Effect of Solvent Type on PAN–Based Nonwoven Nanofibers Membranes Characterizations - Sabeeh, Haneen; Waisi, Basma I. (Iraqi Journal of Chemical and Petroleum Engineering, 2022)
Electrospun nanofiber membranes are employed in a variety of applications due to its unique features. the nanofibers' characterizations are effected by the polymer solution. The used solvent for dissolving the polymer powder is critical in preparing the precursor solution. In this paper, the Polyacrylonitrile (PAN)-based nanofibers were prepared in a concentration of 10 wt.% using various solvents (NMP, DMF, and DMSO). The surface morphology, porosity, and the mechanical strength of the three prepared 10 wt.% PAN-based nanofibers membranes (PAN/NMP, PAN/DMF, and PAN/DMSO) were characterized using the Scanning Electron Microscopy (SEM), Dry-wet Weights method, and Dynamic Mechanical Analyzer (DMA). Using DMF as a solvent resulted in a long, beaded, homogeneous, and smooth surface fibrous structure with an average diameter of 260 nm, which was the best among the solvents tested in this study in terms of porosity and mechanical strength.